Sámi agency in economic development processes in the Norwegian High North - Angell, Elisabeth; Eikeland, Sveinung; Selle, Per (Polar Record, 2023)
The emergence of the Sámi Parliament has lifted Norwegian Sámi politics into an international discourse on indigenous peoples. The clearest imprints of the new Sámi political space are found in the High North region of Norway, where the Sámi account for a significant proportion of the population. The article shows to what extent and how Sámi agency affects governance structures and business development in the north in an increasingly globalised economic setting. From its origin, Sámi agency has influenced development in the High North through three processes: the first is through the Sámi institution building and strengthening of Sámi communities; the second is through its links to local and regional societal development; and the third is through the role of Sámi politics in globalised development processes. One main finding is that the boundaries between these links to the surrounding environment have become more diffuse. Sámi agency is taking a more important role in the economic development processes in the High North, often in terms of the local and regional processes, and now also within the increasingly important globalised economic modernisation processes in which inclusion in new multi-level governance structures is important. publishedVersion